2015
DOI: 10.3389/fnbeh.2015.00048
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of anxiety by cortical serotonin 1A receptors

Abstract: Serotonin (5-HT) plays an important role in the modulation of behavior across animal species. The serotonin 1A receptor (Htr1a) is an inhibitory G-protein coupled receptor that is expressed both on serotonin and non-serotonin neurons in mammals. Mice lacking Htr1a show increased anxiety behavior suggesting that its activation by serotonin has an anxiolytic effect. This outcome can be mediated by either Htr1a population present on serotonin (auto-receptor) or non-serotonin neurons (hetero-receptor), or both. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…Related to the hypothesis that 5-HT functions to moderate aversive mental states ( Deakin and Graeff, 1991 ) and promote patience ( McDannald, 2015 ) is the notion that 5-HT plays an important role in negatively modulating anxiety ( Piszczek et al, 2015 ). Selective reductions of 5-HT in the forebrain have been found to enhance anxiety-related behaviours ( Pum et al, 2009 ; Tu et al, 2014 ), whereas chronically administered SSRIs have been found to reduce anxiety ( Blanco et al, 2013 ).…”
Section: Psychological Functions Associated With Brain 5-htmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to the hypothesis that 5-HT functions to moderate aversive mental states ( Deakin and Graeff, 1991 ) and promote patience ( McDannald, 2015 ) is the notion that 5-HT plays an important role in negatively modulating anxiety ( Piszczek et al, 2015 ). Selective reductions of 5-HT in the forebrain have been found to enhance anxiety-related behaviours ( Pum et al, 2009 ; Tu et al, 2014 ), whereas chronically administered SSRIs have been found to reduce anxiety ( Blanco et al, 2013 ).…”
Section: Psychological Functions Associated With Brain 5-htmentioning
confidence: 99%
“…Selective reductions of 5-HT in the forebrain have been found to enhance anxiety-related behaviours ( Pum et al, 2009 ; Tu et al, 2014 ), whereas chronically administered SSRIs have been found to reduce anxiety ( Blanco et al, 2013 ). Like impulsivity and aggression, anxiety appears to be negatively modulated by 5-HT1AR stimulation ( Heisler et al, 1998 ; Parks et al, 1998 ; Schreiber and De Vry, 1993 ; Toth, 2003 ), and although there are some contradictory findings ( File et al, 1996 ), this effect appears to be mediated by postsynaptic 5-HT1AR signalling ( Celada et al, 2013a ; Gross et al, 2002 ; Piszczek et al, 2015 ; Stefanski et al, 1993 ; Tauscher et al, 2001 ; Tu et al, 2014 ; Zhou et al, 2008 , 2014 ).…”
Section: Psychological Functions Associated With Brain 5-htmentioning
confidence: 99%
“…Stimulation of HTR1A within the hippocampus or amygdala was known to produce an anxiogenic effect, while HTR1A agonist injection into the dorsal raphe nucleus was anxiolytic . Findings from transgenic animals showed that overexpression of HTR1A in forebrain and even in cortical principal neurons could reverse the anxiety phenotype of HTR1A knockout mice . Therefore, we speculate that increasing HTR1A in ACC is likely associated with decreasing anxiety in rats, which need to be researched further.…”
Section: Discussionmentioning
confidence: 99%
“…6,31,32 Findings from transgenic animals showed that overexpression of HTR1A in forebrain and even in cortical principal neurons could reverse the anxiety phenotype of HTR1A knockout mice. 33,34 Therefore, we speculate that increasing HTR1A in ACC is likely associated with decreasing anxiety in rats, which need to be researched further.…”
Section: Consistent Withmentioning
confidence: 91%
“…As reported in other papers. (62)(63)(64) Activation of serotonin receptors may result in anxiolytic response (65), and estrogen may modulate this response (66). Other neurotransmitters and hormones may participate in this response.…”
Section: Discussionmentioning
confidence: 99%